Community-Based Antibiotic Prescribing Attributable to Respiratory Syncytial Virus and Other Common Respiratory Viruses in Young Children: A Population-Based Time-series Study of Scottish Children. (9th April 2020) - Fitzpatrick, Tiffany; Malcolm, William; McMenamin, Jim; Reynolds, Arlene; Guttmann, Astrid; Hardelid, Pia
Abstract: Background: Inappropriate antibiotic prescribing, such as for viral illness, remains common in primary care. The objective of this study was to estimate the proportion of community-prescribed antibiotics to children aged less than 5 years attributable to common respiratory viruses. Methods: We fitted time-series negative binomial models to predict weekly antibiotic prescribing rates from positive viral pathogen tests for the period 1 April 2009 through 27 December 2017 using comprehensive, population-based administrative data for all children (<5 years) living in Scotland. Multiple respiratory viral pathogens were considered, including respiratory syncytial virus (RSV), influenza, human metapneumovirus (HMPV), rhinovirus, and human parainfluenza (HPIV) types 1–4. We estimated the proportion of antibiotic prescriptions explained by virus circulation according to type of virus, by age group, presence of high-risk chronic conditions, and antibiotic class. Results: We included data on 6 066 492 antibiotic prescriptions among 452 877 children. The antibiotic-prescribing rate among all Scottish children (<5 years) was 609.7 per 1000 child-years. Our final model included RSV, influenza, HMPV, HPIV-1, and HPIV-3. An estimated 6.9% (95% confidence interval, 5.6–8.3%), 2.4% (1.7–3.1%), and 2.3% (.8–3.9%) of antibiotics were attributable to RSV, influenza, and HMPV, respectively. RSV was consistently associated with the highest proportion of prescribed antibiotics, particularly among children without chronic conditions and for amoxicillin and macrolide prescriptions. Conclusions: Nearly 14% of antibiotics prescribed to children in this study were estimated to be attributable to common viruses for which antibiotics are not recommended. A future RSV vaccine could substantially reduce unnecessary antibiotic prescribing among children. Abstract : Antibiotic prescribing for viruses is inappropriate and may increase antimicrobial resistance. We estimate that a large proportion of community-prescribed antibiotics in Scottish children is attributable to common respiratory viruses. The highest proportion of antibiotics were attributed to respiratory syncytial virus.